Effect of adjuvants on physicochemical properties of lime sulfur on flower/paraffin and application on flower thinning - Li, Yuanyuan; Liu, Yang; Wu, Changjie; Zhao, Rui; Li, Minghua; Cai, Jing; Ma, Li; He, Xiongkui; Wu, Xuemin; Zhenhua, Zhang (Frontiers in Plant Science, 2023)
Introduction Adjuvants can effectively enhance the utilization rate of pesticides, but the application of adjuvants in plant growth regulators is rarely studied. Methods This work explored the effects of adjuvants dioctyl sulfosuccinate sodium salt (AOT) and methyl oleate (MO) on lime sulfur (LS), especially the drop behavior on flower and paraffin surface. Results The results showed that the addition of AOT and AOT+MO can significantly reduce the static and dynamic surface tension of LS from 72mN/m to 28mN/m and 32mN/m respectively, and increase the spreading factor from 0.18 to 1.83 and 3.10 respectively, reduce the bounce factor from 2.72 to 0.37 and 0.27 respectively. The fluorescence tracer test showed that the addition of adjuvants could promote the spreading and permeation of droplets. The field test results revealed that the flower thinning rate of adjuvant and non-adjuvant were 80.55% and 54.4% respectively, and the flower thinning effect of adding adjuvant was the same as that of artificial which the flower thinning rate was 84.77%. The quality of apples treated with adjuvants was similar to that treated with artificial, and the weight of single fruit increased by 24.08% compared with CK (spray water). Discussion The application of tank-mixture adjuvant could reduce the dosage of LS for thinning agent application, improve apple’s quality, and decrease labor cost and improve the economic benefits of fruit planting and the environmental benefits of plant growth regulators.